The Bibliographical Collections and Archives of the Fundación Alejo Carpentier, Cuba. - Raggi Rodríguez, Armando; Rodríguez Beltrán, Rafael (Caribbean Quarterly)
The article discusses the bibliographical collections and archives of the Fundación Alejo Carpentier (FAC), a cultural non-governmental organization created by Cuban writer Alejo Carpentier's widow Lilia Esteban Carpentier which aims to disseminate his life and work, in Cuba. The FAC has negotiated publishing agreements with publishers in many countries.